Solitary waves observed in the auroral zone: the Cluster multi-spacecraft perspective - Pickett, J.S.; Kahler, S.W.; Chen, L.-J.; Huff, R.L.; Santolík, O.; Khotyaintsev, Y.; Décréau, P.M.E.; Winningham, D.; Frahm, R.; Goldstein, M.L.; Lakhina, G.S.; Tsurutani, B.T.; et al. (My University, 2004)
We report on recent measurements of solitary waves made by the Wideband Plasma Wave Receiver located on each of the four Cluster spacecraft at 4.5-6.5RE (well above the auroral acceleration region) as they cross field lines that map to the auroral zones. These solitary waves are observed in the Wideband data as isolated bipolar and tripolar waveforms. Examples of the two types of pulses are provided. The time durations of the majority of both types of solitary waves observed in this region range from about 0.3 up to 5ms. Their peak-to-peak amplitudes range from about 0.05 up to 20mV/m, with a few reaching up to almost 70mV/m. There is essentially no potential change across the bipolar pulses. There appears to be a small, measurable potential change, up to 0.5V, across the tripolar pulses, which is consistent with weak or hybrid double layers. A limited cross-spacecraft correlation study was carried out in order to identify the same solitary wave on more than one spacecraft. We found no convincing correlations of the bipolar solitary waves. In the two cases of possible correlation of the tripolar pulses, we found that the solitary waves are propagating at several hundred to a few thousand km/s and that they are possibly evolving (growing, decaying) as they propagate from one spacecraft to the next. Further, they have a perpendicular (to the magnetic field) width of 50km or greater and a parallel width of about 2-5km. We conclude, in general, however, that the Cluster spacecraft at separations along and perpendicular to the local magnetic field direction of tens of km and greater are too large to obtain positive correlations in this region. Looking at the macroscale of the auroral zone at 4.5-6.5RE, we find that the onsets of the broadband electrostatic noise associated with the solitary waves observed in the spectrograms of the WBD data are generally consistent with propagation of the solitary waves up the field lines (away from Earth), or with particles or waves propagating up the field line, which leads to local generation of the solitary waves all along the field lines. A discussion of the importance of these solitary waves in magnetospheric processes and their possible generation mechanisms, through electron beam instabilities and turbulence, is provided.
Keywords: Solitary waves; Auroral zone; Multi-spacecraft perspective; Magnetic field